Revealing burden of elevated blood pressure among Polish adolescent participants in a population-based ADOPOLNOR study: prevalence and potent risk factors - Krzyżaniak, Alicja; Stawińska-Witoszyńska, Barbara; Krzywińska-Wiewiorowska, Małgorzata; Siwińska, Aldona; Kaczmarek, Maria (Anthropological Review, 2019)
New category for elevated blood pressure introduced and described by JNC-7 for adults and adopted by the 2004 Working Group for children and adolescents stands for a pre-sign to hypertension. The ongoing rise in prevalence of high blood pressure in children and adolescents demands their regular screening. The objective of this study was to determine prevalence of elevated BP in Polish adolescents and explain the role of sex, age and body weight status as potent risk factors for this condition. A population-based cross-sectional survey was carried out on a sample of 4,941 students (2,451 boys and 2,490 girls) aged 10–18, participants in the ADOPOLNOR study. Body height and weight were measured and BMI was calculated. Blood pressure was measured twice on each visit on the right arm using a fully calibrated TECH MED TM-Z mercury gauge sphygmomanometer with sets of exchangeable cuffs and a clinical stethoscope. The blood pressure classification was determined using the surveillance method. The depended outcome variable was the elevated BP compared to normal BP for systolic (SBP), diastolic (DBP) and combined SBP and/or DBP. Explanatory variables included demographic characteristics, sex and age, and weight status. Two-way ANCOVA, Chi-square Pearson correlation, and multivariate logistic regression analysis (MLRA) were performed using the STATISTICA 13.1 data analysis software system; p-value <0.05 was considered statistically significant (StatSoft Inc. Tulsa, OK, USA). A clear gender pattern was found in prevalence of elevated BP with girls being more likely than boys to have elevated BP (4.9%, 5.3% and 7.4% for SBP, DBP and combined SBP and/or DBP in girls vs 3.5%, 3.5% and 5.9% in boys). The proportion of both genders with elevated BP gradually increased with age with 4.8% (SBP), 2.8% (DBP) and 5.8% (SBP and/or DBP), and 5.1%, 6.4% and 8.4% in early and late adolescence, respectively. Fifteen percent of obese adolescents had elevated SBP, 14.3% elevated DBP and 17.8% had elevated either SBP and/or DBP combined. At multivariate approach, the adjusted odds ratio for predictors of elevated BP revealed sex, age and weight status for SBP and SBP and/or DPB combined. Age and weight status were predictive for elevated DBP. Weight status (BMI) showed the highest predictive potential of elevated BP for both genders. The likelihood of developing elevated BP increased at least twice with each BMI category increase. Thus, overweight and obese adolescents were twice (overweight) and 4 to 5 times (obese) more likely than their normal weight counterparts in developing elevated BP. The study results confirmed predictive potential of sex, age, and weight status in developing elevated BP in adolescents. The highest odds of the weight status indicate that it is the strongest confounder of elevated BP condition.